Lack of association between genotypes and virulence factors in C. albicans strains isolated from vaginal secretion - Shinobu,Cristiane Suemi (2007)
The physiopathogenesis of vulvovaginal candidiasis (VVC) is still not completely elucidated. The objective of this study was to evaluate if there is a relationship between the different genotypes of Candida albicans, their main agent and the virulence of this yeast in vaginal isolates, and to check if there are laboratorial markers that can predict the ability of each isolate to develop VVC independently of symptoms. The production of exoenzymes protease, phospholipase and haemolysin, resistance to hydrogen peroxide, and the genotype were determined. Genotype A was predominant (75%), protease, phospholipase and haemolytic activity were highly expressed, and the majority of the yeasts were sensitive to H2O2 in 1 and 2 hours of exposure, suggesting that these factors are important in the virulence of vaginal isolates. However they did not have any correlation with the genotypes. The different isolates expressed similar virulence potential, suggesting that other factors relating to the yeasts and the host must participate in the development of the clinical disease.